The answer is probably e, π or √2. Issue 5 (4th July 2017) - McCartney, Mark
ABSTRACT: A number of probabilistic experiments are described to estimate e, π and2, with results from computer simulations being used to investigate convergence. A number of possible classroom exercises and extensions are presented.